Proceedings of the Virtual Reality International Conference - Laval Virtual 2018
DOI: 10.1145/3234253.3234306
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Framework For Systemizing the Evaluation of Immersive And Collaborative Performance

Abstract: The capacity to visually represent innovative product/service ideas and concepts as well as usage scenarios while anticipating the resulting User eXperience (UX) is extremely critical in order to ensure innovation success. Our previous empirical studies on low-cost Immersive Virtual Environments (IVE), and, more recently, on Immersive Collaborative Environments (ICE) have unveiled the great potential of 'close-to-real-life' immersion. It fulfills the necessary level of realism in order to engage and facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
10
0
2
Order By: Relevance
“…The above-mentioned series of study takes place in the business sector of rooms furnishing within public, professional or private building spaces. These studies will reuse and extend our previous work on Immersive Virtual Environment (IVE) and Immersive Collaborative Environment (ICE) [3,4,5], including UX [6,7,8], Fuzzy Front-End (FFE) model [9,10] and IX [11].…”
Section: Existing Theories and Previous Workmentioning
confidence: 74%
“…The above-mentioned series of study takes place in the business sector of rooms furnishing within public, professional or private building spaces. These studies will reuse and extend our previous work on Immersive Virtual Environment (IVE) and Immersive Collaborative Environment (ICE) [3,4,5], including UX [6,7,8], Fuzzy Front-End (FFE) model [9,10] and IX [11].…”
Section: Existing Theories and Previous Workmentioning
confidence: 74%
“…First, we searched in the Scopus database articles and conference papers from 2000 to 2020, using the title, abstract and keywords fields. The 20 years period was chosen because as analyzed from the (Dupont et al, 2018) research it was appeared that before 2000 there are few research works on the immersive experience assessment question. The search parameters are presented in Table 1, the search equation used the keywords: Immersive environment (or Virtual) and Biometrics (or Physiological).…”
Section: Field Option Abstractmentioning
confidence: 99%
“…This shows a high potential for the technology as a tool in diverse applications. However, research on co-creation process involving user experience supported by immersive environment still needs more development (Dupont et al, 2018). Indeed, if the Immersive Collaborative Environment (ICE) tree describes the properties of collaborative experience and immersive experience (Dupont et al, 2017), we need to better understand how users interact with those technologies.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in 2018 on collaborative immersive environments (Dupont et al, 2018) provides interesting insights into the notion of trust and co-creation of value. Collaborative immersive environments include tools, methods, digital systems (from Web 2.0 to immersive devices), or even physical spaces that allow and facilitate the work of groups composed of eclectic people, distributed or not, in synchronous or asynchronous work (Recker et al, 2013;Tran, 2014;Bayrak, 2015;Dupont et al, 2018). The analysis, based on 23 scientific articles published since 2000 in international journals and one thesis, highlighted four recurring dimensions for Collaborative eXperience: (1) Sense Making; (2) Trust Building; (3) Shared Meanings; (4) Mutual Understanding.…”
Section: Co-creation Of Value and Trust: Forgotten By Collaborative Ementioning
confidence: 99%
“…This study also identified two properties by dimension, respectively: context understanding and relevance; interpersonal relationships and trust; knowledge sharing and knowledge creation; group dynamics and collective intelligence. Dupont et al (Dupont et al, 2018) reveals that two properties are not very well researched: trust and knowledge creation. The small number of studies on collaborative immersive environments that focus on these properties raises questions about the importance given to concepts that are at the heart of collaborative processes, which are by nature open and by nature part of a knowledge creation process, consubstantial with the innovation process.…”
Section: Co-creation Of Value and Trust: Forgotten By Collaborative Ementioning
confidence: 99%